A comparative study of knowledge regarding emergency care during disaster between community health volunteers working in tsunami-affected and non-affected areas in Aceh Province, Indonesia - Kamal, Anda; Songwathana, Praneed; SaeSia, Wipa (Department of Nursing, Faculty of Medicine, Diponegoro University, 2014)
Purpose: This study aimed to describe and compare the level of knowledge regarding emergency care during disaster between community health volunteers (CHVs) working in the tsunami affected and non-affected areas in Aceh Province, Indonesia.Method: 144 CHVs from six districts in Aceh were studied during November 2011 to January 2012 to evaluate their level knowledge regarding emergency care during disaster between CHVs working in tsunami-affected 6-areas and non-tsunami-affected areas. The knowledge was assessed using the Community Health Volunteers’ Knowledge Regarding Emergency Care Questionnaire (CHVK-ECQ) with 30 true/false statements. The composite scores of each area and the total score were calculated and transformed to percentage for ease of presentation.Results: Overall, the CHVs’ knowledge in emergency care during disaster in Aceh was at a high level in both groups. However, subjects in non-affected areas had significantly higher mean rank of the overall knowledge than those in the affected areas (p = .02). In the tsunami area, the highest mean score of knowledge was in the disaster triage dimension (M= 80.62%), and the lowest mean score was in the first aid (60.48 %). In contrast, CHVs’ knowledge in the non-tsunami areas had the highest mean score in the first aid (84.52 %) and had the lowest mean score in the disaster triage (64. 38 %).Conclusion: Although both groups had high levels of overall knowledge, an education program for improved knowledge in the areas of first aid, team organization, and disaster triage should be emphasized to refresh the CHVs’ knowledge and skills for disaster management.